Bovine parthenogenotes produced by inhibition of first or second polar bodies emission - Bevacqua, Romina Jimena (2011)
Fil: Bevacqua, Romina Jimena. Universidad de Buenos Aires. Facultad de Agronomía. Laboratorio de Biotecnología Animal. Buenos Aires, Argentina.